Differential contribution of TrkB and p75NTR to BDNF-dependent self-renewal, proliferation, and differentiation of adult neural stem cells - Lozano-Ureña, Anna; Frade, José M. (Frontiers in Molecular Neuroscience, 2023)
Alterations in adult neurogenesis are a common hallmark of neurodegenerative diseases. Therefore, understanding the molecular mechanisms that control this process is an indispensable requirement for designing therapeutic interventions addressing neurodegeneration. Neurotrophins have been implicated in multiple functions including proliferation, survival, and differentiation of the neural stem cells (NSCs), thereby being good candidates for therapeutic intervention. Brain-derived neurotrophic factor (BDNF) belongs to the neurotrophin family and has been proven to promote neurogenesis in the subgranular zone. However, the effects of BDNF in the adult subventricular zone (SVZ) still remain unclear due to contradictory results. Using in vitro cultures of adult NSCs isolated from the mouse SVZ, we show that low concentrations of BDNF are able to promote self-renewal and proliferation in these cells by activating the tropomyosin-related kinase B (TrkB) receptor. However, higher concentrations of BDNF that can bind the p75 neurotrophin receptor (p75NTR) potentiate TrkB-dependent self-renewal and proliferation and promote differentiation of the adult NSCs, suggesting different molecular mechanisms in BDNF-promoting proliferation and differentiation. The use of an antagonist for p75NTR reduces the increment in NSC proliferation and commitment to the oligodendrocyte lineage. Our data support a fundamental role for both receptors, TrkB and p75NTR, in the regulation of NSC behavior.